Andrew Shryock: Nationalism and the Genealogical Imagination. Oral History and Textual Authority in Tribal Jordan. - Korsholm Nielsen, Hans Chr. (Tidsskriftet Antropologi, 1998)
Oral History and Textual Authority in Tribal Jordan. Anmeldes af Hans Chr. Korsholm Nielsen